FPGA Implementation For Image Enhancement using Zynq-7020 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital image upgrade strategies can be used to expand the photographic nature of images. The main target of any upgrade technique is to acquire more reasonable result. Image upgrade procedures can be arranged into two techniques: spatial domain and frequency domain techniques. This paper presents and focused on image upgrade in the spatial domain, with specific reference to point prepare strategies include: contrast manipulation, brightness manipulation, inverting images, threshold operation. This undertaking presents an idea of equipment programming for hardware and software co-simulation to image handling and utilizing Xilinx Vivado which is implemented on Zynq -7020 .This strategy, gives a bunch of Simulink blocks (models) for a few equipment activities that could be carried out on different Xilinx FPGAs.